Stability and removal of dexamethasone sodium phosphate from wastewater using modified clays. - Khamis, Mustafa (2014)
Stability and removal of dexamethasone sodium phosphate (DSP) from wastewater produced at Al-Quds University Campus were investigated. Kinetic studies in both pure water and wastewater coming from secondary treatment (activated sludge) demonstrated that the anti-inflammatory DSP underwent degradation to its hydrolytic derivative, dexamethasone, in both media. The first-order hydrolysis rate of DSP in activated sludge at 25 degrees C (3.80 x 10(-6) s-1) was about 12-fold larger than in pure water (3.25 x 10(-7) s-1). The overall performance of the wastewater treatment plant (WWTP) installed in the University Campus was also assessed showing that 90% of spiked DSP was removed together with its newly identified metabolites by the ultra-filtration (UF) system, which consists of a UF hollow fibre (HF) with a 100-kDa cutoff membrane as the pre-polishing stage for the UF spiral wound with a 20-kDa cutoffmembrane. In testing other technologies, the effectiveness of adsorption and filtration by micelle-clay (MC) preparation for removing DSP was ascertained in comparison with activated charcoal. Batch adsorption in aqueous suspensions of the MC composite and activated carbon was well described by Langmuir isotherms showing the best results for MC material. Filtration of DSP water solutions demonstrated a significant advantage of columns filled in with a mixture of sand and MC complex in comparison with activated carbon/sand filters.